New information technologies in social studies: postnonclassical paradigm - Galina Ya. Menshikova; Yury P. Zinchenko; Artem I. Kovalev; Ludmila A. Shaigerova (Национальный психологический журнал, 2015)
The paper discusses topical issues of virtual reality technologies in social research, particularly when studying the processes of ethnic cultural identity, development of ethnic and racial attitudes using «virtual avatars» for managing ethnic conflicts, development of communication skills in representatives of different cultures using virtual collaboration and video conferencing. One of the key issues of the paper to discuss the necessity of post-non-classical paradigm as a conceptual framework for social research. Contemporary social studies require developing new methods, technologies and techniques at all levels of the research: from task setting to the development of new methods and result analysis. One of the most promising methods rapidly developed in recent years is virtual reality technology. The paper presents the analysis of more than 40 experimental studies performed using CAVE and HMD virtual reality systems. Their application is considered hereunder for the studies of verbal and nonverbal cues in communication, social skills training, treatment of social anxiety disorders and the development of new methods of cognitive behavioural therapy. Studies on interpersonal communication with virtual partners (i.e. «avatars») are considered. Factors affecting the communication quality of avatars, its visual and behavioural realism, problems of seeing virtual human as real partners for social interaction are discussed. Special attention is paid to the studies of racial and ethnic attitudes performed using virtual reality systems. The possibilities of practical applications of the VR technologies for shaping positive attitudes and development of communication skills in a sociocultural context are emphasized.